English proficiency and acculturation among Chinese immigrant youth in Canada: a reciprocal relationship. Issue 8 (16th November 2016) - Jia, Fanli; Gottardo, Alexandra; Chen, Xi; Koh, Pohwee; Pasquarella, Adrian
ABSTRACT: The main focus of this study was to refine our understanding of the link between English proficiency and mainstream acculturation in adolescent Chinese immigrants. The sample consisted of 112 adolescents in grades 7–12 living in urban areas in southern Ontario, Canada. English proficiency was assessed individually using standardised tests of vocabulary knowledge, reading comprehension, and reading fluency. Mainstream acculturation was measured by the Vancouver Index of Acculturation. The results of structural equation modelling support a reciprocal relationship between English proficiency and mainstream acculturation after controlling for age, length of residence in Canada, and nonverbal reasoning. The results suggest that learning English may be one important variable affecting motivation for cultural immersion in immigrant youth.